Finite deformation and instability of a rotating cylinder under end thrust. (November 2022) - Fan, Shengjun; Liu, Yanju; Jia, Fei
Abstract: In our work, we investigate systematically the deformation and instability of a rotating cylinder of compressible material under fixed end thrust using Neo-Hookean material model. We employ numerical methods to study the solution of the second order differential equation for the radial deformation, which represents the deformation of the cylinder under loading conditions. We further analyse the instability behaviour of the rotating elastic cylinder using the incremental deformation theory and obtain the critical value of angular velocity when buckling occurs. Finally, we plot a phase diagram, which illustrates the regions of stable, buckling and no solution with respect to angular velocity and end thrust. Highlights: We developed theoretical model of a rotating cylinder under end thrust, adopted numerical methods to investigate its deformation and instability behaviour, and obtained a phase diagram which depicts the regions of "stable", "buckling", and "no solution" with respect to angular velocity and end thrust.